Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
[tex] \left \{ {{y=6x-11} \atop {-2x-3y=-7}} \right. \ \ \ | substitute\ first\ equation\ into \ the\ second\\\\
-2x-3(6x-11)=-7\\\\
-2x-18x+33=-7\\\\
-20x+33=-7\ \ \ | subtract\ 33\\\\
-20x=-40\ \ \ | divide\ by\ -20\\\\
x=2\\\\
y=6x-11=6*2-11=12-11=1[/tex]
just subsitute 6x-11 for y in the second equation
-2x-3(6x-11)=-7
-2x-18x+33=-7
-20x+33=7
subtract 33 from both sides
-20x=-40
multiply -1
20x=40
dividede by 20
x=2
then subsitute
y=6x-11
y=6(2)-11
y=12-11
y=1
x=2
y=1
-2x-3(6x-11)=-7
-2x-18x+33=-7
-20x+33=7
subtract 33 from both sides
-20x=-40
multiply -1
20x=40
dividede by 20
x=2
then subsitute
y=6x-11
y=6(2)-11
y=12-11
y=1
x=2
y=1
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.